2019
DOI: 10.1084/jem.20181604
|View full text |Cite
|
Sign up to set email alerts
|

Sox8 is essential for M cell maturation to accelerate IgA response at the early stage after weaning in mice

Abstract: Microfold (M) cells residing in the follicle-associated epithelium (FAE) of the gut-associated lymphoid tissue are specialized for antigen uptake to initiate mucosal immune responses. The molecular machinery and biological significance of M cell differentiation, however, remain to be fully elucidated. Here, we demonstrate that Sox8, a member of the SRY-related HMG box transcription factor family, is specifically expressed by M cells in the intestinal epithelium. The expression of Sox8 requires activation of RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
85
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(93 citation statements)
references
References 48 publications
(92 reference statements)
1
85
0
Order By: Relevance
“…To identify OPG-expressing cells in the FAE, we performed whole-mount immunostaining of the FAE using the FAE-sheet ( Fig. 1d) 13,14 . We used three M-cell markers: Tnfaip2, GP2, and Spi-B.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To identify OPG-expressing cells in the FAE, we performed whole-mount immunostaining of the FAE using the FAE-sheet ( Fig. 1d) 13,14 . We used three M-cell markers: Tnfaip2, GP2, and Spi-B.…”
Section: Resultsmentioning
confidence: 99%
“…We previously defined GP2 as a hallmark of M-cell full maturation: Spi-B + GP2 high cells are mature M cells that vigorously take up luminal antigens, whereas Spi-B + GP2 -/low cells are immature M cells with lower capacity to take up luminal antigens 13,14 SIgA is the most abundant class of antibodies found on the mucosal surface; these antibodies play important roles in protection against pathogens and in the regulation of the gut microbial community 38 . We previously reported that the IgA response is gradually enhanced during the development of DSS-induced colitis 39 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…M cells are specialised enterocytes normally present in the follicle associated epithelium (FAE) that overlies mucosal lymphoid tissues, such as the small intestinal Peyer’s patches, and equivalents in the nasopharyngeal tract and lung (Date et al, 2017; Kimura et al, 2014; Kimura et al, 2019b; Mabbott et al, 2013). In the intestines, daughter cells derived from Lgr5+ intestinal stem cells at the intestinal crypt base differentiate into M cells upon RANKL stimulation (de Lau et al, 2012) and expression of the transcription factors Spi-B (Kanaya et al, 2012) and Sox8 (Kimura et al, 2019a). M cells transport antigens from the mucosal surface into lymphoid tissues to immune cells that inhabit a unique pocket structure at their basal side (Kolesnikov et al, 2020; Komban et al, 2019).…”
Section: Introductionmentioning
confidence: 99%